2015
DOI: 10.1007/s00259-015-3088-4
|View full text |Cite
|
Sign up to set email alerts
|

Could semiquantitative FDG analysis add information to the prognosis in patients with stage II/III breast cancer undergoing neoadjuvant treatment?

Abstract: The addition of WB TLG to clinical data may provide a more detailed prediction of outcome in patients with stage III BC. Moreover, WB MTV and WB TLG are independent factors predicting recurrence of BC. On the contrary, WB SUVmax has poor prognostic significance in this cohort of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 22 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…In particular, Galán et al [ 25 ] failed to identify a role of volumetric parameters in pCR prediction. Conversely, Evangelista et al [ 26 ] showed a predictive value of TLG_WB for DFS, and Hyun et al [ 27 ] reported that the variation of MTV_WB was predictive for OS at multivariate analysis in BC patients treated with NAC. However, these studies considered BC patients regardless of the molecular subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Galán et al [ 25 ] failed to identify a role of volumetric parameters in pCR prediction. Conversely, Evangelista et al [ 26 ] showed a predictive value of TLG_WB for DFS, and Hyun et al [ 27 ] reported that the variation of MTV_WB was predictive for OS at multivariate analysis in BC patients treated with NAC. However, these studies considered BC patients regardless of the molecular subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of locally advanced BC (LABC) usually differs from that of early BC (EBC) as in LABC, surgery is usually preceded by neoadjuvant chemotherapy (NAC) [ 85 ]. However, NAC indications are have been widely debated in the literature after recent evidence suggested consideration of NAC in TNBC and HER-2-positive BC, regardless of disease extension [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…The use of volumetric parameters extracted from [ 18 F]FDG PET/CT is another promising tool to assess response after NAC in BC patients [ 50 ]. In particular, Evangelista et al [ 51 ] reported for the first time that baseline TLG could predict disease-free survival. Similarly, Urso et al [ 52 ] reported that the SUVmean of the primary tumor at baseline [ 18 F]FDG PET/CT was higher in Luminal-B patients achieving pCR after NAC.…”
Section: Discussionmentioning
confidence: 99%